Water balance modeling in Mediterranean water limited ecosystem using vegetation parameters and soil moisture from remote sensing - Detto M.; Mancini M.; Martinelli J.; Montaldo N. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
In this paper we present an application of the combined use of remote information and hydrological modeling on a monitored basin in the Italian semi arid area, using the remote sensing analysis for hydrological model parameterization and model validation. In fact we retrieve at pixel scale vegetation parameter as the leaf area index (LAI) used in the computation of evapotraspiration and surface soil moisture images used as 'internal' control variable of model behavior. The LAI is obtained from Quikcbird satellite using visible and near infrared images while the soil moisture is retrieved from microwave ASAR (Advanced Synthetic Aperture Radar on the European Space Agency satellite Envisat). Discussion of result is then provided in term of data reliability with perspective of operative use as aid in the irrigation practice and in a real time monitoring of fluxes between land surfaces and the atmosphere boundary layer.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)